The Role of Cloud Accounting in Improving MSME Performance in The Digital Economy Era - AlPutri Oktavia; Ayke Nuraliati; Liza Ulfiana (Oikonomia : Journal of Management Economics and Accounting, 2025)
This study examines the role of cloud accounting in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in the digital economy era. Using a mixed academic review and empirical narrative approach, the study synthesizes 34 relevant academic publications, policy documents, and industry reports from 2019 to 2024. Findings reveal that cloud accounting offers substantial benefits to MSMEs, including improved operational efficiency, enhanced financial accuracy, real-time cash flow monitoring, and accelerated financial reporting. Cloud-based accounting systems also strengthen business transparency and creditworthiness, enabling MSMEs to gain better access to formal financing opportunities. Integration with digital payment systems, e-commerce platforms, and business management applications supports MSMEs in expanding their presence within the digital ecosystem. Despite these advantages, adoption barriers remain, particularly among micro-enterprises in rural areas. Key challenges include limited digital literacy, unequal technological infrastructure, concerns regarding data security, and perceptions of subscription fees as a financial burden. This study recommends a collaborative strategy among government institutions, technology providers, financial institutions, and universities to promote cloud accounting adoption through education, infrastructure development, user support systems, and financial incentives. The study contributes to MSME digital transformation discourse and provides practical insights for policymakers and business owners seeking to enhance competitiveness in an increasingly data-driven economic environment.